Diagnostic value of the pediatric lower urinary tract symptom score in children with overactive bladder - ŞİMŞEK, FERRUH; TİNAY, İLKER; TARCAN, TUFAN; ŞENER, TARIK EMRE (SPRINGER, 2014)
The aims were (1) to assess the pediatric lower urinary tract symptom score (SS) prior to treatment as a means of determining severity of overactive bladder (OAB) and (2) to investigate relationships between SS results and those of standard diagnostic modalities. Symptom scores were recorded pre- and 6 months SS for 294 children with OAB unrelated to neurological disorder. Uroflowmetry-electromyography data, total bladder capacity, and a 2-day bladder diary were also recorded, and upper urinary tract deterioration was investigated as indicated. Overactive bladder was treated with standard approaches. No response to treatment was defined as 0-49 % reduction in OAB-related symptoms based on SS results. Non-responders underwent additional evaluations as indicated. Two hundred forty-one patients (97 %; mean age 9.8 +/- A 2.8 years; mean follow-up 11 months; range 6-18 months) completed the study. One hundred thirteen (47 %) required ultrasonography (USG), and those with abnormal USG had a significantly higher pre- and 6 months SS (p = 0.016). All non-responders (n = 38; 16 %) underwent urodynamics evaluation, 34 underwent spinal magnetic resonance imaging (MRI), 34 underwent voiding cystourethrography (VCUG), and 34 underwent dimercaptosuccinic acid scanning (DMSA). Non-responders with terminal detrusor hyperactivity had significantly lower SS after therapy (p = 0.09). Non-responders with abnormal MRI had higher pre- and 6 months SS than those with normal MRI. Thirteen (38 %) of the non-responders who required VCUG had vesicoureteral reflux (VUR), and this subgroup had higher pre-treatment SS (p = 0.030). Seven (21 %) of the non-responders who required DMSA had scarring, and all 7 had VUR. The subgroup with scarring had higher pre-treatment SS (p = 0.030). Pediatric OAB patients with high 6 months SS have a higher incidence of additional upper urinary tract pathology. Those with low pre-treatment SS require fewer laboratory tests and other assessments. The SS tool can reduce the number of urodynamics evaluations, and other tests required to diagnose renal damage in children with OAB.
Keywords: Symptom score; Voiding dysfunction; Treatment; Ultrasonography; Voiding cystourethrogram; VESICOURETERAL REFLUX; VOIDING DYSFUNCTION; SYSTEM; POPULATION; STANDARDIZATION; ADOLESCENTS; PREVALENCE; ENURESIS; SOCIETY